Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.17158/222
|View full text |Cite
|
Sign up to set email alerts
|

Jigsaw Approach in Cooperative Learning: Its Effect in Problem Solving Skills for Physics

Abstract: This study was conducted to determine whether or not the jigsaw approach as a cooperative learning strategy can significantly improve the problem solving skills in physics of the First Year Pharmacy students of the University of the Immaculate Conception for School Year 2011-2012. The researchers used the quasi-experimental design and purposively chose one class with forty students to compose the experimental group and another class of the same size to form the control group. The students from the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The students' scores in the posttest were now This gives the researchers the idea that the students who are part of the group who are assigned to learn and discuss to their groupmates the sub-topic about environment and values did a great job in doing their tasks. This idea is supported by Limjuco & Gravino (2012) wherein in their study, they found out that students who were exposed to the Jigsaw strategy improved their proficiency, responsibility, facilitation, and approachability as learners. The students believed that studying is important for both themselves and their fellow group members.…”
Section: Research Questionsmentioning
confidence: 84%
“…The students' scores in the posttest were now This gives the researchers the idea that the students who are part of the group who are assigned to learn and discuss to their groupmates the sub-topic about environment and values did a great job in doing their tasks. This idea is supported by Limjuco & Gravino (2012) wherein in their study, they found out that students who were exposed to the Jigsaw strategy improved their proficiency, responsibility, facilitation, and approachability as learners. The students believed that studying is important for both themselves and their fellow group members.…”
Section: Research Questionsmentioning
confidence: 84%